Intensive blood pressure control may not be safe in subacute ischemic stroke by intracranial atherosclerosis: a result of randomized trial. Issue 9 (September 2018) - Park, Jong-Moo; Kim, Bum Joon; Kwon, Sun U.; Hwang, Yang-Ha; Heo, Sung Hyuk; Rha, Joung-Ho; Lee, Jun; Park, Man-Seok; Kim, Joon-Tae; Song, Hee-Jung; Park, Jong-Ho; Yu, Sungwook; et al.
Abstract : Objective: Current guideline recommends intensive blood pressure (BP) control in hypertensive patients, but the appropriate target BP level after ischemic stroke due to intracranial atherosclerotic stenosis remains uncertain. Methods: In this randomized, single-blinded trial, patients with symptomatic internal carotid or middle cerebral artery steno-occlusion (>50%) within 7–42 days after index stroke received intensive (target SBP < 120 mmHg) or modest (target SBP < 140 mmHg) BP control from April 2010 to December 2012. The primary outcome was the change in ischemic lesion volume in white matter lesions at the whole forebrain between baseline and 24 weeks as measured from fluid attenuation inversion recovery (FLAIR) images, which was tested in noninferiority test (noninferiority margin of 3 cm 3 ). Results: Among 132 patients, follow-up FLAIR images were available in 111 (59 in the intensive and 52 in the moderate BP control groups). After 24 weeks, the SBP in the intensive group was significantly lower (124.6 ± 10.5 mmHg) than in the modest group (132.3 ± 10.6 mmHg). The ischemic lesion volume increased more in the intensive group (4.9 ± 18.3 cm 3 ) than the modest group (2.2 ± 8.2 cm 3 ), which failed to prove noninferiority. The frequency of new ischemic lesions on 24-week FLAIR images was nonsignificantly higher in the intensive group than the modest group [10 (16.9%) vs. 5 (9.6%), respectively; P  = 0.26)]. Only one recurrent stroke developed during the study period in each group. Conclusion: Intensive BP control in intracranial atherosclerotic stenosis patients failed to prove noninferiority compared with modest BP control, and may increase ischemic lesion volume in the subacute stage. Abstract : Supplemental Digital Content is available in the text